How do I look: The role of Brand Anthropomorphism and Implicit Self-Theories on Brand Evaluations? - Nimra Ali; Muhammad Sheeraz (South Asian Management Research Journal, 2023)
Nowadays marketing practitioners are more interested to make a lifetime bond with consumers. Previous research studies have shown that brand anthropomorphism enhances consumer brand evaluations in terms of likability, positive sentiments, purchase intentions, and trust in that particular brand. Research reveals that consumers show a favorable attitude toward brands that are anthropomorphized. According to the implicit-personality theory, there are two broad human personalities, one who believes that people have fixed traits (“entity theorists”) while others deem that people's personality is malleable (“incremental theorists”). However, less work is done to investigate this brand anthropomorphism-evaluation process in contingency with the personality of consumers. Hence this study aims to examine the role of implicit theory in brand humanization evaluation phenomena. The results validate the existing research that anthropomorphizing the brands not only enhances consumer attitude towards the brand but also generates more trust and likeliness of purchase. Conversely, study data did not support the proposed hypothesis that the brand anthropomorphizing evaluation process is less positive for entity theorists. Nevertheless, this process remains same for the incremental theorists.
Keywords: 330; Brand Anthropomorphism; Implicit Self-Theories; Entity Theorists; Incremental Theorists; Brand Evaluations; Attitude toward Brand; Brand Trust; Purchase Intentions